2022
DOI: 10.1111/jonm.13835
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress and moral injury and their interplay as a challenge for leadership and management: The case of Croatia

Abstract: Aim We aim to investigate the interplay between moral distress and moral injury among nurses working in palliative and oncology wards and to assess its impact on nursing leadership. Background The past 2 years have been particularly challenging for nurses and nursing leaders in Croatia. The coronavirus disease pandemic and the subsequent earthquakes in the country significantly impacted the work of nurses. Moral distress has been well‐known to nursing professionals, but recent studies warn about cofounding it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The PRISMA flowchart delineates the review process (see figure 1). Of the 81 full texts included in the review,6 12–21 43–112 some reported multiple studies in the same paper, so there were 88 separate studies included in the review. Of these, six reported prevalence estimates or average scores that could not be pooled, so they were included in the narrative synthesis only.…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flowchart delineates the review process (see figure 1). Of the 81 full texts included in the review,6 12–21 43–112 some reported multiple studies in the same paper, so there were 88 separate studies included in the review. Of these, six reported prevalence estimates or average scores that could not be pooled, so they were included in the narrative synthesis only.…”
Section: Resultsmentioning
confidence: 99%
“…MD has the potential to affect all categories of healthcare professionals, across a variety of settings, in countries throughout the world. [1][2][3][4] The concept of MD in health care was described in the early 1980s, 5 and a wealth of research has been published on the topic since then, especially within nursing literature. Sustained MD can lead to moral injury 6 which often manifests as impaired function or prolonged psychological harm; other features of moral injury include anxiety, depression, anger, grief, withdrawal, feelings of shame, compassion fatigue, a desire to seek alternative employment and difficulty sleeping.…”
mentioning
confidence: 99%
“…MD has the potential to affect all categories of healthcare professionals, across a variety of settings, in countries throughout the world. 1 4…”
mentioning
confidence: 99%